Observations of Phαceliα tαnαcetifoliα as a Food Plant for Honey Bees and other insects - Thrasyvoulou, Andreas; Tsirakoglou, Basilis (ENTOMOLOGIA HELLENICA, 1998)
Three consecutive sowings of Phacelia tanacetifolia Bentham (Hydrophyllaceae) were examined for plant growth and attractiveness to bees and other insect-visitors over a three years’ study. Plants that were sown in March flowered uniformly for periods of 24 to 40 days, while those sown in June and July had a non-uniform anthesis that was impossible to estimate. Plants sown in early August, remained vegetative throughout winter and flowered the following spring. Maximum visits of honey bees were observed between 10:00 h and 17:00 h. Most honey bees (>70%) collected nectar. Seasonal differences in the ratio nectar/pollen gatherers were noted. Two species of bumble bee (B. terrestris and B. lucorum) and 9 species of solitary bee visited Phacelia.